Nano-electronic devices using two-dimensional and phase change materials - Sarwat, S (2018)
This thesis describes nanoscale devices utilizing phase change and two-dimensional materials. The fundamentals, modeling, chip design, nano-fabrication process, measurement setups and experimental results of such devices are discussed. In the first example, a graphene-nano-gap phase change memory device concept is proposed, in which a phase change material bridges graphene electrodes that are spaced sub-1 nm apart. These devices are fabricated using a lithography-free self-alignment technique. The manufacture and metrology of such devices are studied, with a demonstration of a Kelvin Probe Microscopy based approach for in-situ imaging. Such devices enable ultra-scaled memory cells for energy efficient operation. Scaling limit of such devices are studied and an intrinsic gap length is found below which carbon filamentation overwhelms resistive switching in the phase change material. The second example features the study of electronic properties of two-dimensional materials under external perturbation, such as strain. A new approach based on Kelvin Probe Microscopy is demonstrated to overcome the limitations (materials, resolution and substrate effects) of commonly used optical spectroscopy tools, and reveals strain-driven changes in the work functions, including junction potentials in ultrathin heterostructures. A device concept termed strain-effect transistor is proposed wherein two-dimensional materials can be strained cyclically by the reversible amorphous-crystalline phase transition in the underlying phase change material. Crucially, a chalcogenide glass with high volume changes is explored for this application. The volume changes in the material are observed to complement changes in optical properties and are further exploited for a demonstration of solid-state reflective displays and tunable photonic resonators. The third example reveals the light-matter interaction in low dimensional phase change materials using graphene nano-gaps and crossbar nanoscale devices. Contrary to the existing understanding of these interactions, the complex interplay of three independent mechanisms, viz. photoconductive, photo induced-crystallization and photo-induced-thermoelectric effects, are observed to govern the photoresponse of the material. Significant photovoltaic effects are observed in such devices, which might lead to phase change devices for photonic applications being potentially self-powered. The photodetection bandwidth and photo-responsivity are observed to be tunable based on the state of the phase change material, enabling the development of tunable photodetectors. Finally, the concept of a spiking photodetector is introduced that utilizes the strong-light matter coupling in chalcogenide glasses. Such devices could be used in the development of artificial retinas.